Teacher Strategies in Developing Students Emotional Competence in English Language Learning: A Narrative Inquiry Study - Jannah, Nurul; Hizriani, Nani (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Learning English is difficult, particularly for non-native speakers who have to become proficient in not just grammar and vocabulary but also emotional competency to convey clearly. Language acquisition is significantly influenced by emotional competence, which is the capacity to identify, comprehend, and regulate one's own and others' emotions. This study is to look at the ways English language teachers use to help their students become emotionally competent. This study gathers interview data using a narrative inquiry technique to expose the lived experiences and perspectives of English teachers. The study of the data emphasizes trends and narratives showing how emotional competency is included into English instruction methods. The results show that teachers successfully enhance students' emotional competency by using contextual textbooks, presentations, English songs, observational assessments, and honest evaluations among other approaches. This study adds to the body of knowledge on emotional intelligence in the classroom and has application for curriculum creation and teacher preparation programs. This study aims to explore teachers’ strategies in developing students’ emotional competence and their impact on the success of English language learning through a narrative inquiry approach. The findings offer practical insights for improving teacher training and curriculum development in order to support a balanced integration of students’ emotional and academic development